2015
DOI: 10.1111/nph.13562
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplication and divergence affecting drug content in Cannabis sativa

Abstract: SummaryCannabis sativa is an economically important source of durable fibers, nutritious seeds, and psychoactive drugs but few economic plants are so poorly understood genetically.Marijuana and hemp were crossed to evaluate competing models of cannabinoid inheritance and to explain the predominance of tetrahydrocannabinolic acid (THCA) in marijuana compared with cannabidiolic acid (CBDA) in hemp. Individuals in the resulting F 2 population were assessed for differential expression of cannabinoid synthase genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
210
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(228 citation statements)
references
References 44 publications
16
210
1
1
Order By: Relevance
“…4). GC analysis of chemotype II has typically demonstrated a more narrow range skewed towards a high CBD total to THC total ratio (De Meijer et al 1992;Hillig and Mahlberg 2004;Weiblen et al 2015), although a low CBD total to THC total ratio similar to those reported here have been observed in Southeast Asian landraces (Tipparat et al 2012). Nevertheless, this is the first time that such a wide range in chemotype II variability has been unequivocally assigned to genotype and heterozygosity of THCAS and CBDAS.…”
Section: Chemotype II Variabilitymentioning
confidence: 41%
See 3 more Smart Citations
“…4). GC analysis of chemotype II has typically demonstrated a more narrow range skewed towards a high CBD total to THC total ratio (De Meijer et al 1992;Hillig and Mahlberg 2004;Weiblen et al 2015), although a low CBD total to THC total ratio similar to those reported here have been observed in Southeast Asian landraces (Tipparat et al 2012). Nevertheless, this is the first time that such a wide range in chemotype II variability has been unequivocally assigned to genotype and heterozygosity of THCAS and CBDAS.…”
Section: Chemotype II Variabilitymentioning
confidence: 41%
“…All things being equal chemotype II individuals would be expected to have a CBD total :THC total ratio close to 1:1. Deviation from this ratio within chemotype II has previously been proposed to be due either to increased catalytic efficiency of CBDA synthase over THCA synthase (Weiblen et al 2015), or from genetic vs environment interactions (Potter 2009). Considering that ratios of chemotype II plants deviated both towards CBD total and THC total , and that all plants were grown in environmentally controlled conditions, it could be suggested that chemotype II variability is largely influenced by genetic control.…”
Section: Chemotype II Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…A single locus with co-dominant alleles was proposed to explain patterns of inheritance for THCA to CBDA ratios (de Meijer et al, 2003;Staginnus et al, 2014). However more recent quantitative trait loci (QTL) mapping experiments (Weiblen et al, 2015), expression studies (Onofri et al, 2015), and genomic analyses (van Bakel et al, 2011) paint a more complex scenario with several linked paralogs responsible for the various THCA and CBDA phenotypes. Other cannabinoids such as cannabigerol (CBG) (Borrelli et al, 2014), cannabichromene (CBC) (Izzo et al, 2012), and delta-9-tetrahydrocannabivarin (THCV) (Mcpartland et al, 2015) demonstrate pharmacological promise, and can also be produced at high levels by the plant (de Meijer and Hammond, 2005;de Meijer and Hammond, 2016;de Meijer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%